Does a Dedicated Unit for the Treatment of Hip Fractures Improve Acute Outcomes?. (20th November 2014) - Khoriati, Al-achraf; Dandachli, Wael; Deol, Rupinderbir; de Roeck, Nicholas
Abstract : The aim of this study is to establish whether management of patients in a unit dedicated to the treatment of hip fractures improves acute outcomes. We prospectively studied 300 patients with hip fractures in two separate groups. Patients in Group 1 were operated on in a mixed trauma unit and recovered in a traditional trauma ward. Patients in Group 2 were operated on in dedicated theatres and recovered in a unit which catered exclusively for hip fractures. The ages, ASA grades, and type of procedure performed in the two groups were comparable. The 30-day mortality rate in Group 2 was 9% as opposed to 12% in Group 1 (P = 0.34 ). The inpatient length of stay was significantly lower in Group 2 (18 days versus 25 days; P = 0.0002 ) and so was the time taken to operate (28 hours versus 34 hours; P = 0.04 ). A greater percentage of patients in Group 2 were discharged home as opposed to a nursing home (75% versus 67%). This difference approached significance (P = 0.18 ). We conclude that prioritisation and prompt management of patients with hip fractures in a dedicated unit significantly improve time to surgery and significantly decrease length of stay.